Y-6=64

Simple and best practice solution for Y-6=64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-6=64 equation:


Simplifying
Y + -6 = 64

Reorder the terms:
-6 + Y = 64

Solving
-6 + Y = 64

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + Y = 64 + 6

Combine like terms: -6 + 6 = 0
0 + Y = 64 + 6
Y = 64 + 6

Combine like terms: 64 + 6 = 70
Y = 70

Simplifying
Y = 70

See similar equations:

| 2x^4+2x^2-12=0 | | 129=-3x+3(2x+35) | | 12x+5+23x=180 | | X-.26x=629 | | -2(t-2)+5t=6t-11 | | -19-12x=14x+35 | | 3x+2(-4+0.5)=1 | | X^3+279=0 | | 6x=100+2x | | 12x+5=23x | | -221+12x=23x+230 | | -5(a+1)=49(a+10) | | 9x-20=28+x | | 14p+21-8=14p+13 | | 180=90+4x+2x | | 11x-159=x+331 | | y-4=2(x-6) | | 5=-12+n | | 21x-27=22x+29 | | 3(2x+5)-x=2x+15 | | 3=6p-21 | | -317+14x=147-2x | | 12=k-5 | | 15=r+5 | | 6u=-48 | | -(-3-2x)-5= | | -35-14x=21-16x | | 10x^2-16x-6=0 | | 5x+17y=91 | | (-2i)(-8i)(2)= | | 4-6x=x+11 | | -56+24=22x+22 |

Equations solver categories